Developmental Stage-Specific Distribution of Macrophages in Mouse Mammary Gland - Stewart, Teneale A.; Hughes, Katherine; Hume, David A.; Davis, Felicity M. (Frontiers in Cell and Developmental Biology, 2019)
Mammary gland development begins in the embryo and continues throughout the reproductive life of female mammals. Tissue macrophages (Ms), dependent on signals from the M colony stimulating factor 1 receptor (CSF1R), have been shown to regulate the generation, regression and regeneration of this organ, which is central for mammalian offspring survival. However, the distribution of Ms in the pre- and post-natal mammary gland, as it undergoes distinct phases of development and regression, is unknown or has been inferred from immunostaining of thin tissue sections. Here, we used optical tissue clearing and 3-dimensional imaging of mammary tissue obtained from Csf1r-EGFP mice. Whilst tissue Ms were observed at all developmental phases, their abundance, morphology, localization and association with luminal and basal epithelial cells exhibited stage-specific differences. Furthermore, sexual dimorphism was observed at E14.5, when the male mammary bud is severed from the overlying epidermis. These findings provide new insights into the localization and possible functions of heterogeneous tissue M populations in mammogenesis.